(untitled) (Ameghiniana, 2013)
The species of Kulopterts (X. elongata, X. rigida, X. argentina and X. spinifolia) ha ve been studied with the optical and electronic (SEM) microscope. Materials from dífferents localitíes from. the Míddle and Upper Triassic of Argentine, Upper Triassic of Australia and Upper Triassic of South Afnca have been used.